Variables with a negative impact on the quality of life of gays and lesbians in Spain: evaluation of homophobic and lesbophobic indicators to guide youth education - García-Sánchez, José-Rufino; Gago-Valiente, Francisco-Javier; López-López, María-José; Segura-Camacho, Adrián; Saenz-de-la-Torre, Luis-Carlos; Moreno-Sánchez, Emilia (Frontiers in Psychology, 2024)
Background Despite the evidence about the negative impact of homophobic and lesbophobic attitudes on the quality of life of these individuals, the World Health Organisation (WHO) continues to report a lack of research and understanding regarding the health of gays and lesbians and LGTB people in general. There is a growing commitment in public health to understand and improve the health and well-being of LGTB people, and it is very important that professionals in social, educational and health care settings are adequately trained and informed to solve the problems that persist in this population. The aim of this study was to identify homophobic and lesbophobic attitudes in a Spanish youth population, analyzing the relationship of these attitudes with sociodemographic, cultural, political and personal variables. Methods A descriptive, cross-sectional study was carried out with 325 young people aged 18–30 years. The information was collected through the Modern Homophobia Scale of Raja & Stokes, in which sociodemographic and sociocultural variables were also gathered. The data were analyzed and correlations were estimated. Results The males showed a more negative attitude toward homosexual people compared to the females. The participants with a higher education level presented more positive attitudes toward homosexual people. Younger people with a heterosexual orientation had more negative attitudes toward homosexual people compared to those with a homosexual orientation. The participants with a stronger right-wing political tendency presented a greater percentage of negative attitudes toward LGTB people. Conclusion Variables such as education level, sexual orientation and political ideology may have a significant influence on the attitudes toward homosexual men and/or lesbian women. Different results were obtained as a function of sex, thus it is important to consider the gender perspective in future studies that tackle this topic.